Eradication of endophytic bacteria via treatment for axillary buds of Petunia hybrida using Plant Preservative Mixture (PPMTM) - Miyazaki, J.; Tan, Beng; Errington, Steve (Springer, 2010)
Plant Preservative Mixture (PPMTM), a proprietary mixture of two broad-spectrum isothiazolone biocides, was recently introduced as a prophylactic anti-bacterial agent in plant tissue culture. Its efficacy for eradicating endophytic Sphingomonas paucimobilis in Petunia hybrida was tested. The presence of bacterial cells in intercellular spaces of parenchyma tissues in the cortex and pith, in the lumen of xylem vessels and within sclerenchyma cells, could be detected in histo-sections by both light and transmission electron microscopy. The eradication protocol involved infiltration of infected axillary buds with PPM solution under vacuum. Quantitation by high performance liquid chromatography (HPLC) revealed that axillary buds from upper young nodes absorbed significantly more PPM compared with those from the lower nodes. Indexation indicated successful eradication of bacterial contaminants from upper young axillary buds after vacuum-infiltration with 5 ml l−1 PPM.